Hybrid Dysfunction Expressed as Elevated Metabolic Rate in Male Ficedula Flycatchers - McFarlane SE; Sirkia PM; Alund M; Qvarnstrom A (PUBLIC LIBRARY SCIENCE, 2022)
Studies of ecological speciation are often biased towards extrinsic sources of selection against hybrids, resulting from intermediate hybrid morphology, but the knowledge of how genetic incompatibilities accumulate over time under natural conditions is limited. Here we focus on a physiological trait, metabolic rate, which is central to life history strategies and thermoregulation but is also likely to be sensitive to mismatched mitonuclear interactions. We measured the resting metabolic rate of male collared, and pied flycatchers as well as of naturally occurring F1 hybrid males, in a recent hybrid zone. We found that hybrid males had a higher rather than intermediate metabolic rate, which is indicative of hybrid physiological dysfunction. Fitness costs associated with elevated metabolic rate are typically environmentally dependent and exaggerated under harsh conditions. By focusing on male hybrid dysfunction in an eco-physiological trait, our results contribute to the general understanding of how combined extrinsic and intrinsic sources of hybrid dysfunction build up under natural conditions.